Analysis of Financial performance affecting Stock Price on Pharmaceutical Industry - Rusky Aviandy (Universitas Trisakti, 2007)
This research is conducted to analyze the influence of stock price of firms in the pharmaceutical industry as listed in the JSX using financial ratios and based on the Gordon model approach. Methodology used in this research was Gordon model to know the stocks intrinsic value from each firm, then the comparison of market stock price, and analysis using regression analysis to know which factors affect stock price and how big the influence is. This research used six research variables; ROA, ROE, payout ratio, book value per share. and debt to equity ratio. The research population was pharmaceutical companies listed on the JSX until the end of 2004. It can be concluded that ROA, ROE,book value per share, and debt to equity has a very weak influence to stock price. Only payout ratio has the significant influence to stock price of firm in the pharmaceutical industry listed on the JSX. There is significant effect from return on asset, return on equity, payout ratio, book value per share and debt toequity ratio altogether to market price of firms in pharmaceutical industry.